CoNiFe oxide nanostructure catalyst and application thereof

The challenge of direct conversion of methane into value-added chemicals was solved by using an electrochemical catalyst that combines Co1-xNixFe2O4 nanocubes with carbon, achieving high-efficiency electrochemical oxidation of methane into methanol, and demonstrating the dual purpose of the catalyst, suitable for a variety of electrochemical reactions.

CN119563053APending Publication Date: 2025-03-04UNIVERSITY OF GUELPH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046743.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-16
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to develop efficient, adjustable selective catalysts for direct conversion of methane into value-added chemicals, especially in electrochemical conversion, where there are challenges in C-H activation and product selectivity.

Method used

Co1-xNixFe2O4 nanocube trimetal oxide is used as an electrochemical catalyst and combined with carbon to form a Co1-xNixFe2O4/carbon catalyst, which is used to convert methane to methanol in electrochemical reactions.

Benefits of technology

The efficient electrochemical oxidation conversion of methane to methanol is achieved, which improves the activity and selectivity of the catalyst. The catalyst exhibits dual purpose in the conversion of methane and nitrogen, and is suitable for a variety of reactions in electrochemical processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563053A_ABST
    Figure CN119563053A_ABST
Patent Text Reader

Abstract

The present disclosure relates to CoNiFe nanostructured catalysts, and the use of such catalysts in the electrochemical conversion of methane to methanol. In particular, the present disclosure relates to nanocube catalysts having the formula Co < 1-x > Ni < x > Fe < 2 > O < 4 >.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to U.S. Provisional Application No. 63 / 353,182, filed on June 17, 2022, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates to CoNiFe nanostructured catalysts and the use of such catalysts in the electrochemical conversion of methane to methanol. In particular, the present disclosure relates to nanostructured catalysts having the formula Co 1-x Ni x Nanocube catalyst of Fe2O4. Background Art

[0004] Methane (CH4) is not only the second most important greenhouse gas causing global warming, 1 , but also potentially useful raw materials that can be converted into valuable products for the chemical industry. 2-4 In view of the worsening environmental problems and the inevitable depletion of fossil fuel energy, there is an urgent need to develop efficient and environmentally friendly strategies for improving the direct conversion of methane (DMC) to value-added chemicals. 5-7 The traditional Fischer-Tropsch process for methanol synthesis relies primarily on converting syngas (a mixture of CO and H2) into useful chemicals through energy-intensive reactions, which makes the process economically and environmentally unsustainable. 8 In addition, CH activation of CH4 molecules and overoxidation of products also greatly limit the conversion kinetics and selectivity of CH4 oxidation. 2 Therefore, the development of highly active catalysts with tunable selectivity is crucial for the efficient conversion of CH4. In recent years, the conversion of CH4 into oxygenates has gained great attention in the fields of resource management and carbon capture. Therefore, many alternative strategies have been explored to develop DMC technology using liquid phase reactions involving catalysis, 9 Enzyme catalysis, 10 Biocatalysis, 11 Photocatalysis, 8 and electrocatalysis. 12 Electrocatalytic CH4 oxidation offers an attractive and environmentally friendly approach to efficiently generate valuable chemical products due to its low cost, controllable reaction, and ease of large-scale production. Efficient electrocatalysts for CH4 conversion are essential to improve the thermodynamics and kinetics of the process compared to the competing oxygen evolution reaction (OER).

[0005] People have been committed to exploring high-performance electrocatalysts, 13,14 Electrochemical reaction cell design, 15,16Incorporation of microorganisms 11,17 or solar cells, 18,19 and density functional theory (DFT) calculation techniques 20,21 To promote the conversion of CH4 and its utilization under ambient conditions. Despite the significant progress achieved so far in the field of CH4 conversion, one of the great challenges that still remain for the optimal oxidation of CH4 is the design of highly active electrocatalysts for CH activation and product selectivity. In this regard, the development of efficient electrocatalysts for the conversion of DMC to oxygenates is a key prerequisite. Summary of the invention

[0006] The present disclosure relates to CoNiFe nanostructured catalysts and the use of such catalysts in the electrochemical conversion of methane to methanol. In particular, the present disclosure relates to nanostructured catalysts having the formula Co 1-x Ni x Nanocube catalyst of Fe2O4.

[0007] In one embodiment of the present disclosure, an electrochemical catalyst is included, comprising:

[0008] (a) a trimetallic oxide of the following formula

[0009] Co 1-x Ni x Fe2O4

[0010] wherein the catalyst is in the form of nanocubes; and

[0011] (b) Carbon.

[0012] In one embodiment, the electrochemical catalyst of the present disclosure is used for the electrochemical oxidation of methane.

[0013] In one embodiment of the present disclosure, there is included a method for producing methanol from methane in an electrochemical process, the process comprising:

[0014] (a) introducing methane into an anode chamber of an electrochemical reactor, wherein the anode chamber comprises an anode comprising an electrochemical catalyst of the present disclosure;

[0015] (b) introducing a catholyte into a cathode chamber of the electrochemical reactor, wherein the cathode chamber comprises a cathode;

[0016] (c) introducing a voltage between the anode and the cathode, thereby oxidizing at least a portion of the methane to methanol; and

[0017] (d) collecting the methanol from the anode chamber.

[0018] Other features and advantages of the present application will become apparent from the following detailed description. However, it should be understood that although the detailed description and specific examples indicate the preferred embodiments of the present application, they are only given by way of illustration, because various changes and modifications within the spirit and scope of the present application will become apparent to those skilled in the art based on this detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present disclosure will now be described in more detail with reference to the accompanying drawings, in which:

[0020] Figure 1 (a) SEM image and (b) corresponding size distribution of NiFe PBA template catalyst; (c) NiFe PBA template was heated to 2℃ min-1 under air condition. 1 (d) images of CoNiFe-N / C catalyst inks with different ratios in one embodiment of the present disclosure.

[0021] Figure 2 It's CoyNi 1-y - SEM images of Fe2O4-N / C catalysts, respectively (a) y = 0, (b) y = 0.2, (c) y = 0.4, (d) y = 0.6, (e) y = 0.8, and (f) y = 1

[0022] Figure 3 In one embodiment of the present disclosure, CoyNi 1-y -SEM images of Fe2O4-N / C catalysts, respectively (a) y=0, (b) y=0.2, (c) y=0.4, (d) y=0.6, (e) y=0.8, and (f) y=1.

[0023] Figure 4 In one embodiment of the present disclosure, CoyNi 1-y - SEM images of Fe2O4 catalysts, respectively (a) y=0, (b) y=0.2, (c) y=0.4, (d) y=0.6, (e) y=0.8, and (f) y=1.

[0024] Figure 5 (a) CoyNi under air and Ar conditions, respectively 1-y - Average size of Fe2 PBA derived catalysts; (b) Scheme of the structure proposed for PBA particles in CoFeNi in one embodiment of the present disclosure. The ratio between core and shell is arbitrary.

[0025] Figure 6(a)-(b) are LSV curves of CoNiFe-N / C-0.8 and CoNiFe-8 in Ar-saturated and N2-saturated 0.1M Na2SO4 solutions, respectively; (c)-(d) are LSV curves of CoNiFe-N / C-0.6 and CoNiFe-0.6 in Ar-saturated and CH4-saturated 0.5M Na2CO3 solutions, respectively, in one embodiment of the present disclosure. Scan rate: 20 mV s -1 .

[0026] Figure 7 (a)-(e) are LSV curves of CoNiFe-N / Cx (x = 0, 0.2, 0.4, 0.6, 1) catalysts in Ar-saturated and N2-saturated 0.1 M Na2SO4 solutions, respectively, with a scan rate of 20 mV s -1 (f) The corresponding current density difference of the CoNiFe-N / C catalyst measured in N2 saturated solution and Ar saturated solution in one embodiment of the present disclosure.

[0027] Figure 8 (a)-(e) are LSV curves of CoNiFe-x (x = 0, 0.2, 0.4, 0.6, 1) catalysts in Ar-saturated and N2-saturated 0.1 M Na2SO4 solutions, respectively, with a scan rate of 20 mV s -1 (f) The corresponding current density difference of the CoNiFe-x catalyst measured in N2 saturated solution and Ar saturated solution in one embodiment of the present disclosure.

[0028] Fig. 9 (a)-(e) are LSV curves of CoNiFe-N / Cx (x = 0, 0.2, 0.4, 0.8, 1) catalysts in Ar-saturated CH4-saturated 0.5 M Na2CO3 solution, respectively, with a scan rate of 20 mV s -1 (f) In one embodiment of the present disclosure, the current density difference of the CoNiFe-N / Cx catalyst measured in a CH4 saturated solution and an Ar saturated solution.

[0029] Fig.10 (a)-(e) are LSV curves of CoNiFe-x (x = 0, 0.2, 0.4, 0.8, 1) catalysts in Ar-saturated CH4-saturated 0.5 M Na2CO3 solution, respectively, with a scan rate of 20 mV s -1 (f) In one embodiment of the present disclosure, the current density difference of the CoNiFe-x catalyst measured in a CH4 saturated solution and an Ar saturated solution.

[0030] Fig.11 YesCo 0.6 Ni0.4 -Fe2O4-N / C catalyst: (a) TEM image; (b) HRTEM image; (c) TEM mapping. 0.8 Ni 0.2 -Fe2O4-N / C catalyst: (d) TEM image; (e) HRTEM image; (f) TEM mapping.

[0031] Fig.12 The constructed crystal structure is as follows: (a) bulk Co y Ni 1-y Fe2O4, (b) Co y Ni 1-y Fe2O4-CH3, (c)Co y Ni 1-y Fe2O4-N2, (d)Co y Ni 1-y Fe2O4-N / C and (e)Co y Ni 1-y Fe2O4-N / C-CH3, (e)Co y Ni 1-y Fe2O4-N / C-N2

[0032] Fig.13 In one embodiment of the present disclosure, a crystal Co is constructed y Ni 1-y Fe2O4(a) and Co y Ni 1-y Simulated XRD pattern of Fe2O4-N / C (b) model.

[0033] Fig.14 (a) XRD pattern and (b) Raman spectrum of as-prepared CoNiFe-N / Cx catalyst.

[0034] Fig.15 is the XPS measurement scan of the prepared CoNiFe-N / Cx catalyst, where x refers to the Co substitution content of Ni atoms; high-resolution XPS spectrum of the CoNiFe-N / Cx catalyst regarding Co 2p (b), Ni 2p (c), Fe 2p (d), C 1s (e) and N1s (f).

[0035] Fig.16 : is a high-resolution XPS spectrum of CoNiFe-N / Cx catalyst with respect to N1s in one embodiment of the present disclosure.

[0036] Fig.17(a) Distribution of nitrogen species in CoNiFe-N / Cx catalysts; (b) high-resolution XPS spectra of O1s in CoNiFe-N / Cx catalysts and their corresponding distribution of oxygen species (c); (d) distribution of O latt / O v ratio.

[0037] Fig.18 : is a high-resolution XPS spectrum of CoNiFe-N / Cx catalyst with respect to O1s in one embodiment of the present disclosure.

[0038] Fig.19 The following are the EIS spectra: (a) Co under Ar saturation and N2 saturation conditions 0.8 Ni 0.2 Fe2O4-N / C catalyst; (b) CoNiFe-N / C catalysts with various composition ratios under N2 saturation conditions [Inset: equivalent circuit model (points: original data; lines: fitted data)]; (c) Co under Ar saturation conditions and CH4 saturation conditions 0.6 Ni 0.4 Fe2O4-N / C catalyst; (d) CoNiFe-N / C catalysts of various composition ratios under CH4 saturated conditions in one embodiment of the present disclosure [Inset: equivalent circuit model].

[0039] Fig. 20 Comparison of the ECSA of (a) CoNiFe-N / C-0.4, (b) 0.6, and (c) 0.8 composites based on their double layer capacitance using CV at 10 to 100 mV s -1 (d) The corresponding plot of current density versus scan rate at -0.75 V in an embodiment of the present disclosure.

[0040] Fig.21 Comparison of the ECSA of (a) CoNiFe-N / C-0.4, (b) 0.6, and (c) 0.8 composites based on their double layer capacitance using CV at 10 to 100 mV s -1 (d) The corresponding plot of current density at 1.0 V versus scan rate in an embodiment of the present disclosure.

[0041] Fig. 22 is a chronoamperometric curve of NRR recorded at different potentials on CoNiFe-NC-0.8 catalyst in one example of the present disclosure.

[0042] Fig.23(a) shows the NH3 production and corresponding FE of CoNiFe-N / C-0.8 after two hours of electrolysis at different potentials; (b) the NH3 production and corresponding FE of CoNiFe-N / Cx and CoNiFe-x (c) after two hours of electrolysis at -1.4 V (relative to Ag / AgCl); 0.6 Ni 0.4 Product analysis of electrochemical CH4 oxidation under Fe2O4-N / C at different potentials: (d) Product analysis after two hours of electrolysis 1 H-NMR spectrum; (e) product yields and FE of methanol and 2-propanol (f); (g) schematic diagram of the integrated electrochemical system for simultaneous CH4 oxidation and N2 reduction; (h) anodic current density of CH4 oxidation with or without NRR in the cathode chamber; (i) chronoamperometric curve of NRR at -0.8 V (relative to Ag / AgCl) in the cathode chamber in one embodiment of the present disclosure.

[0043] Fig.24 (a) is a calibration curve for detecting N2H4 concentration; (b) is a UV-vis spectrum of the cathode chamber solution after two hours of electrolysis under Ar saturated conditions and N2 saturated conditions in one embodiment of the present disclosure.

[0044] Fig.25 In one embodiment of the present disclosure, at different applied potentials, 0.6 Ni 0.4 Product yield percentage of DMC over Fe2O4-N / C catalyst.

[0045] Fig.26 In one embodiment of the present disclosure, 0.6 Ni 0.4 EPR spectra of electrochemical CH4 oxidation on Fe2O4-N / C catalyst (DMPO-·O2 formed in 0.3 M methanol dispersion) - ; Blue (middle): open circuit voltage condition; Red (top): with potential).

[0046] Fig. 27 In one embodiment of the present disclosure, the adsorption energies of CH4 adsorption on the surfaces of CoNiFe-x and CoNiFe-N / Cx catalysts are compared.

[0047] Fig.28 is the PDOS of the following: (a) Co 0.6 Ni 0.4 Fe2O4-N / C and (b)Co 0.8 Ni 0.2Fe2O4-N / C surface; (c) and (d) the corresponding PDOS of CH4 and N2 adsorption, respectively, in one embodiment of the present disclosure. (The inset shows the electron density difference between the four optimized structures, blue area: electron-rich; red area: electron-deficient).

[0048] Fig.29 is the PDOS of the following carbon layers in one embodiment of the present disclosure: (a) Co 0.6 Ni 0.4 Fe2O4-NC and (b)Co 0.6 Ni 0.4 Fe2O4-NC surface and the corresponding CH4 adsorption (c) and N2 adsorption (d). DETAILED DESCRIPTION

[0049] (I) Definition

[0050] Unless otherwise stated, the definitions and embodiments described in this section and elsewhere are intended to apply to all embodiments and aspects of the application described herein to which they apply, as will be understood by those skilled in the art.

[0051] As used herein, the term "comprise" and its derivatives are intended to be open-ended terms that specify the presence of stated features, elements, components, groups, integers and / or steps, but do not exclude the presence of other unstated features, elements, components, groups, integers and / or steps. The foregoing also applies to words with similar meanings, such as the terms "including", "having" and their derivatives.

[0052] As used herein, the term "consisting of" and its derivatives are intended to be closed terms that specify the presence of stated features, elements, components, groups, integers and / or steps, but exclude the presence of other unstated features, elements, components, groups, integers and / or steps.

[0053] As used herein, the term "consisting essentially of" is intended to specify the presence of stated features, elements, components, groups, integers and / or steps, as well as the presence of those features, elements, components, groups, integers and / or steps that do not materially affect the basic and novel characteristics of the features, elements, components, groups, integers and / or steps.

[0054] As used herein, terms of degree such as "substantially", "about" and "approximately" mean a reasonable amount of deviation of the modified term so that the end result is not significantly changed. These terms of degree should be interpreted as including a deviation of at least ± 5% of the modified term, provided that the deviation does not negate the meaning of the word it modifies.

[0055] As used in this application, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise.

[0056] In embodiments comprising an "additional" or "second" component, the second component as used herein is chemically different from the other components or the first component. A "third" component is different from the other, first and second components, and further listed or "additional" components are similarly different.

[0057] As used herein, the term "and / or" means that the listed items exist or are used alone or in combination. In fact, the term means "at least one" or "one or more" of the listed items are used or present.

[0058] As used herein, the term "nanocube" refers to a structural atomic arrangement of a tri-metal oxide in a cubic form, the dimensions of which have nanometer-scale dimensions, for example, about 10 nanometers to 1 micrometer.

[0059] As used herein, the term "carbon" includes both non-graphite forms of carbon and graphite forms of carbon.

[0060] As used herein, the term "adjacent" in reference to the carbon layer and the nanocubes means that the two are in close proximity to each other with little or no intervening open space.

[0061] As used herein, the term "layer" refers to a layer of carbon atoms or molecules on a substrate that is adjacent to or proximate to the tri-metal oxide nanocubes.

[0062] (II) Electrochemical Catalyst

[0063] The present disclosure relates to highly active electrochemical catalysts for the efficient conversion of methane to methanol. In addition, the same catalysts can be used to convert nitrogen to ammonia.

[0064] Thus, in one embodiment, the present disclosure relates to an electrochemical catalyst comprising:

[0065] (i) a trimetallic oxide of the formula,

[0066] Co 1-x Ni x Fe2O4

[0067] wherein the catalyst is in the form of nanocubes; and

[0068] (ii) Carbon.

[0069] In one embodiment, the trimetallic oxide is Co 0.8 Ni 0.2 Fe2O4.

[0070] In one embodiment, the trimetallic oxide is Co 0.6 Ni 0.4 Fe2O4.

[0071] In one embodiment, the catalyst has XRD peaks at 18.28°, 26.15°, 35.69°, and 43.36°.

[0072] In further embodiments, x is an integer between 0.01 and 0.99 or 0.1 to 0.9.

[0073] In another embodiment, x is about 0.20, about 0.40, about 0.60, or about 0.80.

[0074] In one embodiment, the carbon is elemental carbon. In one embodiment, the carbon may contain other atoms (such as oxygen or nitrogen) that do not affect the catalytic activity of the electrochemical catalyst of the present disclosure.

[0075] In another embodiment, the elemental carbon is graphite or graphene.

[0076] In one embodiment, the carbon is in the form of a layer adjacent to the nanocubes.

[0077] In one embodiment, carbon (optionally in the form of a layer) is a structure of carbon atoms that are bound together by covalent, ionic or other strong intramolecular forces. The layer can be flat or undulating. In one embodiment, there are more than one carbon layer, which can be bound together via intermolecular forces (such as van der Waals interactions). Examples of carbon layers include, but are not limited to, graphite layers, graphene sheets, and carbon films. A carbon layer can also refer to a carbonaceous coating that coats the outer surface of a nanocube.

[0078] In one embodiment, the size of the nanocubes with adjacent carbon layers is between 10 nm and 1000 nm.

[0079] In one embodiment, the size of the nanocubes with adjacent carbon layers is between 500 nm and 700 nm.

[0080] In one embodiment, the size of the nanocubes with adjacent carbon layers is between 600 nm and 700 nm.

[0081] In one embodiment, the size of the nanocubes with adjacent carbon layers is between 640 nm.

[0082] (III) Electrochemical process

[0083] The present disclosure relates to electrochemical catalysts for efficiently converting methane into methanol and efficiently converting nitrogen into ammonia. Therefore, in one embodiment of the present disclosure, a method for preparing methanol from methane in an electrochemical process is included, the process comprising:

[0084] (a) introducing methane into an anode chamber of an electrochemical reactor, wherein the anode chamber comprises an anode comprising an electrochemical catalyst of the present disclosure;

[0085] (b) introducing a catholyte into a cathode chamber of the electrochemical reactor, wherein the cathode chamber comprises a cathode;

[0086] (c) introducing a voltage between the anode and the cathode, thereby oxidizing at least a portion of the methane to methanol; and

[0087] (d) collecting the methanol from the anode chamber

[0088] In another embodiment, the process also produces isopropanol.

[0089] In one embodiment, the electrochemical catalyst is Co 0.6 Ni 0.4 Fe2O4.

[0090] In one embodiment, the voltage is between 0.5V and 1.5V.

[0091] In one embodiment, the present disclosure also relates to a method for producing ammonia from nitrogen (N2) in an electrochemical process, the process comprising:

[0092] (a) introducing ammonia into a cathode chamber of an electrochemical reactor, wherein the cathode chamber comprises a cathode comprising an electrochemical catalyst of the present disclosure;

[0093] (b) introducing an anolyte into an anode compartment of the electrochemical reactor, wherein the anode compartment comprises an anode;

[0094] (c) introducing a voltage between the anode and the cathode, thereby reducing at least a portion of the nitrogen to ammonia; and

[0095] (d) collecting the ammonia from the cathode chamber

[0096] In another embodiment, the electrochemical catalyst is Co 0.8 Ni 0.2 Fe2O4.

[0097] In one embodiment, the voltage is between 0.5V and 1.5V.

[0098] In another embodiment, the catalyst of the present disclosure is dual-purpose and can be used as an anode and cathode in an electrochemical process for producing methanol from methane and ammonia from nitrogen in an electrochemical process comprising:

[0099] (a) introducing methane into an anode chamber of an electrochemical reactor, wherein the anode chamber comprises an anode comprising an electrochemical catalyst of the present disclosure;

[0100] (b) introducing ammonia into a cathode chamber of an electrochemical reactor, wherein the cathode chamber comprises a cathode comprising an electrochemical catalyst of the present disclosure;

[0101] (c) introducing a voltage between the anode and the cathode, thereby oxidizing at least a portion of the methane in the anode chamber to methanol and reducing at least a portion of the nitrogen in the cathode chamber to ammonia; and

[0102] (d) collecting the methanol from the anode chamber and collecting the ammonia from the cathode chamber

[0103] In one embodiment, the electrochemical catalyst in the anode compartment is Co 0.6 Ni 0.4 Fe2O4.

[0104] In one embodiment, the electrochemical catalyst in the cathode chamber is Co 0.8 Ni 0.2 Fe2O4.

[0105] In one embodiment, the voltage is between 0.5V and 1.5V.

[0106] Although the present disclosure has been described in conjunction with the specific embodiments of the present disclosure, it is apparent that many alternatives, modifications and variations are apparent to those skilled in the art. Therefore, it is contemplated that all such alternatives, modifications and variations that fall within the spirit and broad scope of the appended claims are encompassed. In addition, the citation or identification of any reference in this application should not be understood as an admission that the reference is available as prior art to the present invention.

[0107] Examples

[0108] The operation of the present disclosure is illustrated by the following representative examples. As will be apparent to one skilled in the art, many details of the examples may be varied while still practicing the disclosure described herein.

[0109] Experimental Section

[0110] Chemicals

[0111] Nickel (II) nitrate hexahydrate (99%, Ni(NO3)2·6H2O), cobalt (II) nitrate hexahydrate (98%, Co(NO3)2·6H2O), sodium citrate (99%, Na3C6H5O7), potassium hexacyanoferrate (III) (99%) + , K4Fe(CN)6), sodium sulfate (99%, Na2SO4), sodium carbonate (99% + , Na2CO3), sodium hydroxide (97% + , NaOH), sodium salicylate (99%, C7H5O3Na), sodium hypochlorite (5%, NaClO), sodium nitrosoferrocyanide (III) (99% + , C5FeN6Na2O), hydrazine (98% + , N2H4) and ammonium chloride (99% + , NH4Cl) was purchased from Sigma-Aldrich Chemical Reagent Co., Ltd. Nafion (1 wt%) solution, hydrogen peroxide (30%, H2O2), sulfuric acid (99% + ), methanol, and ethanol were purchased from Aladdin Co., Ltd. All reagents were of analytical grade and used without further purification. In addition, anion exchange membrane (AEM) was purchased from DuPont (N2050TX, thickness: 0.3 mm). Deionized (DI) water (18.2 MΩ cm) used in all experiments was obtained from Nanopure Diamond TM Ultrapure water system.

[0112] Synthesis of NiFe PBA NC templates: Uniform Ni-Fe PBA nanocubes (NCs) were synthesized via our previously reported method. 4 In a typical procedure, 6 mmol Ni(NO3)2·6H2O and 9 mmol Na3C6H5O7 were dissolved in 200 mL deionized (DI) water to form solution A. At the same time, 4 mmol K4Fe(CN)6 was dissolved in another 200 mL DI water to form solution B. Subsequently, solution B was added dropwise to solution A under magnetic stirring for 20 min. Afterwards, the mixed solution was aged at room temperature for 24 h. Subsequent collection by centrifugation and washing with water and ethanol was performed, and the precipitate was dried at 60 ° C overnight.

[0113] Synthesis of NiFe2O4 and NiFe2O4-N / C NC: Two as-prepared NiFe PBA samples (200 mg each) were heated at 2 °C min-1 in air and Ar atmospheres, respectively. -1The heating rate was further pyrolyzed at 350 °C for 2 h. After cooling, 110.8 mg and 112.4 mg were obtained, which were attributed to NiFe2O4 and NiFe2O4-N / C NC, respectively. The catalyst carbonization yield was calculated as follows:

[0114] Catalyst yield (%) = (m 碳化 / m 催化剂前体 )*100%

[0115] Preparation of CoNiFe-x PBA NC template: CoNiFe-xPBA nanocubes (NCs) were synthesized using the same method as the synthesis of NiFe PBA. In a typical route, the content of Co was used to replace the Ni ions in NiFe PBA so that the total amount of Co and Ni precursor was 6 mmol, where x refers to the Co content (x = 0.2, 0.4, 0.6, 0.8). For example, to prepare a sample with x = 0.2, 4.8 mmol Ni(NO3)2·6H2O, 1.2 mmol Co(NO3)2·6H2O, and 9 mmol Na3C6H5O7 were dissolved in 200 mL DI water to form solution A. At the same time, 4 mmol K4Fe(CN)6 was dissolved in another 200 mL DI water to form solution B. Subsequently, solution B was added dropwise to solution A under magnetic stirring for 20 min. Afterwards, the mixed solution was aged at room temperature for 24 h. The precipitate was separated and purified by centrifugation, and washed with DI water and ethanol; it was then dried at 60° C. overnight to obtain CoNiFe-0.2PBA NC, CoNiFe-0.4PBA NC, CoNiFe-0.6PBA NC, and CoNiFe-0.8PBA NC samples.

[0116] Co y Ni 1-y Fe2O4 and Co y Ni 1-y Synthesis of Fe2O4-N / C NC: Two prepared CoNiFe-x PBA NCs (200 mg each) were heated at 2 °C min-1 in air and Ar atmosphere. -1 The heating rate was further pyrolyzed at 350 °C for 2 h. After cooling, 121.8 mg, 134.2 mg, 130 mg and 122.2 mg were obtained in air atmosphere, which were attributed to Co 0.2 Ni 0.8 Fe2O4 NC, Co 0.4 Ni 0.6 Fe2O4 NC, Co 0.6 Ni 0.4 Fe2O4 NC and Co 0.8 Ni 0.2Fe2O4 NC. Meanwhile, under Ar atmosphere, they were 144.2 mg, 154.2 mg, 134.6 mg, and 127.2 mg, corresponding to Co 0.2 Ni 0.8 Fe2O4-N / C NC、Co 0.4 Ni 0.6 Fe2O4-N / C NC、Co 0.6 Ni 0.4 Fe2O4-N / C NC and Co 0.8 Ni 0.2 Fe2O4-N / C NCs.

[0117] Preparation of CoFe PBA NC template: CoFe PBA nanocubes (NC) were prepared using the same method as the synthesis of NiFe PBA. 6mmol Co(NO3)2·6H2O and 9mmol Na3C6H5O7 were dissolved in 200mL DI water to form solution A. At the same time, 4mmol K4Fe(CN)6 was dissolved in another 200mL DI water to form solution B. Thereafter, solution B was added dropwise to solution A under magnetic stirring for 20min. Thereafter, the mixed solution was aged at room temperature for 24h. Subsequent collection was performed by centrifugation and washed with water and ethanol; the precipitate was dried at 60°C overnight, and the obtained sample was named CoFe PBA NC.

[0118] Synthesis of CoFe2O4 and CoFe2O4-N / C NCs: Two as-prepared CoFe PBA NC samples (200 mg) were heated at 2 °C min-1 in air and Ar atmosphere, respectively. -1 The pyrolysis was further performed at 350 °C for 2 h at a heating rate of 0.1%. After cooling, 107.8 mg and 124.2 mg were obtained, which were attributed to CoFe2O4 and CoFe2O4-N / C NC, respectively.

[0119] Electrochemical measurements: The prepared Co was measured using an electrochemical workstation (Voltalab Potentiostat PGZ301) in a single cell (30 mL) with the required gas inflow system. y Ni 1-y Fe2O4-N / C and Co y Ni 1-y Electrochemical characterization of Fe2O4-N / C catalysts. 5 mg of each prepared sample was dispersed in a mixed solution of 480 μL ethanol, 480 μL water and 40 μL Nafion (0.5 wt%) and ultrasonicated for 60 min. The obtained catalyst ink (10 μL) was coated on a fully polished and cleaned glassy carbon electrode ( 0.071cm 2) as the working electrode. Saturated Ag / AgCl and graphite rod Used as reference electrode and counter electrode, respectively. For nitrogen reduction reaction (NRR), ultrapure nitrogen (99.999%) was purged into the electrolyte solution for at least 20 min to reach saturation before the electrochemical experiment. 0.1M Na2SO4 solution was selected as the electrolyte for all electrochemical nitrogen reduction experiments. To test the CH4 oxidation activity, ultrapure CH4 gas (99.999%) was purged into 0.5MNa2CO3 solution, which was used as the electrolyte for the CH4 oxidation reaction. In order to evaluate the hydrogen evolution behavior and other interferences, measurements were performed under argon saturation and open circuit potential conditions, respectively.

[0120] Linear sweep voltammetry (LSV) was used to evaluate the catalytic activity under Ar-saturated, N2-saturated, and CH4-saturated conditions (scan rate: 20 mV s -1 To determine the electrochemical surface areas (ECSA) of these catalysts, the NRR (electrolyte: 0.1 M Na2SO4) and CH4 (electrolyte: 0.5 M Na2CO3) oxidation reactions were performed under different conditions at different scan rates (10, 20, 30, 40, 50, 60, 70, 80, 90, 100 mV s -1 ) recorded cyclic voltammograms (CV) of these electrocatalysts in the bilayer region. Using electrochemical impedance spectroscopy (EIS) (10 -2 -10 5 Hz) to study the charge transfer resistance of NRR and DMC. All experiments were carried out at room temperature (20±2℃).

[0121] like Figure 1 As shown in a, the field emission scanning electron microscopy (FE-SEM) image shows that hollow Ni-Fe NCs with an average size of 208 nm ( Figure 1 b). The weight loss of the template was studied by thermogravimetric analysis. Figure 1 As shown in Fig. c, the first stage of weight loss at nearly 80 °C can be explained by the loss of surface water molecules. The second stage of weight loss (340 °C) is attributed to the transformation of the PBA structure to the final metal oxide. As illustrated in Scheme 1, by adjusting the Co / Ni ratio and the Co y Ni 1-y The thermal conversion of Fe-PBA at 350 °C under Ar conditions converted the CN of PBA to - The groups are transformed into N-doped carbon layers (N / C), in which Co, Ni, and Fe species are transformed into CoNiFe oxides. 32Meanwhile, the color of the CoNiFeO-N / Cx (x refers to the Co ratios 0, 0.2, 0.4, 0.6, 0.8, and 1) catalyst ink changes to dark brown with increasing Co doping content ( Figure 1 d) Considering the role of the carbon layer in the electrochemical reaction, a carbon-free catalyst was also discussed, in which Co y Ni 1-y Fe-PBA was ripened to form CoNiFeO-x catalyst.

[0122]

[0123] The morphology of the as-prepared CoNiFe catalyst was examined by FE-SEM. Figure 2 As shown in , with the increase of Co content, they exhibited similar nanocube (NC) morphology when processed under Ar conditions; however, the size of the CoNiFe-N / Cx catalysts ( Figure 3 ) and the microstructure changes significantly due to the growth of the carbon layer. At the same time, when treated under air conditions, e.g. Figure 4 As shown in the results, they maintained similar frameworks, and the surface of the CoNiFe-x catalyst became cleaner without the generation of a carbon layer, indicating that the carbon layer can be removed by treatment under air conditions. All CoNiFe PBA samples showed higher yields when treated under Ar conditions than when treated under air conditions (Table 1), further confirming that a carbon layer was generated on the surface of the CoNiFe catalyst under Ar pyrolysis. Interestingly, both yields showed similar distribution trends with increasing Co content, which may be attributed to metal-support interactions. 33 In addition, Figure 5 The average size of the CoNiFe catalyst was calculated and analyzed in a, which is positively correlated with the Co atomic content. Figure 5 As shown in b, the size of these NCs with carbon layer increases from 207 nm to 640 nm with the addition of Co. In the absence of carbon layer, it increases from 162 nm to 475 nm, indicating that the size fluctuation may be mainly attributed to the formation of carbon layer. The elemental composition of CoNiFe-N / C catalyst was studied using energy dispersive X-ray spectroscopy (EDS) (Table 2), which explains that N-doped carbon is generated from CoNiFe PBA.

[0124] In order to explore the electrochemical redox performance of the Co / Ni ratio catalysts, linear sweep voltammetry (LSV) was used to evaluate the electrochemical activities towards NRR and DMC. Figure 6 a and Figure 6 b and Figure 7 and Figure 8As shown in Figure 5, cathodic scans of LSV of catalysts with a range of Co / Ni composition ratios were recorded in Ar-saturated and N2-saturated 0.1 M Na2SO4 solutions for comparison, revealing that the composition of CoNiFe to carbon layer support greatly affects the NRR activity. Figure 7 f and Figure 8 f shows the current density difference of LSV measured in N2-saturated electrolyte and Ar-saturated electrolyte, revealing that Co 0.8 Ni 0.2 The Fe-N / C catalyst showed the highest catalytic activity for NRR. Meanwhile, the CH4 oxidation performance in Ar-saturated and CH4-saturated 0.5 M Na2CO3 electrolytes was Figure 6 c and Figure 6 d, both CoNiFe-N / C-0.6 and CoNiFe-0.6 exhibit high CH4 electrochemical oxidation behavior. Fig. 9 and Fig.10 As shown in , the LSV curve also proves that the anode current density of the CoNiFe-N / C catalyst shows significant improvement relative to the CoNiFe catalyst. Compared with the sample without carbon layer, the calibration curve further indicates that the starting CH4 oxidation potential at CoNiFe-N / C is lower, with the lowest being 0.49V (relative to Ag / AgCl) at CoNiFe-0.4. Although the starting potential of CoNiFe-N / C is 0.54V, it shows significant anode current density for CH4 oxidation. In short, the CoNiFe-N / C-0.6 catalyst is used as an optimized electrode for CH4 oxidation reaction. Based on the above data and analysis, the carbon layer support of CoNiFe oxide will be beneficial to improve the electrochemical performance, especially for NRR and DMC.

[0125] To further explore the crystal structures of these catalysts, transmission electron microscopy (TEM), crystal model construction, and X-ray diffraction patterns (XRD) were used. Fig.11 ), the optimized CoNiFe-N / C-0.8 and CoNiFe-N / C-0.6 catalysts exhibited a cubic structure composed of nanoparticles, and the carbon film can also be easily seen. High-resolution TEM (HRTEM) images ( Fig.11 b and Fig.11 e) depicts the lattice fringes of 0.209 nm, 0.252 nm, and 0.482 nm, which may be attributed to the crystal planes (002), Co y Ni 1-yThe crystal planes (311) of Fe2O4 and (111) of CoFe2O4 were also found. In addition, the lattice constant of amorphous carbon was found to be 0.342 nm on the edge of the cube, which corresponds to the (002) crystal plane, indicating that the crystal structure of the synthesized catalyst is Co y Ni 1-y Fe2O4-N / C.Co y Ni 1- The lattice fringes of yFe2O4 intersect with those of CoFe2O4, indicating the formation of a heterojunction. In addition, TEM mapping images demonstrate the uniform metallic mixing of the Co, Ni, and Fe composites ( Fig.11 c and Fig.11 f). These results confirm the successful synthesis of Co in our study. y Ni 1-y Fe2O4-N / C catalyst. In addition, some lattice fringes were destroyed, indicating that some defects were generated. Based on these data, the Co y Ni 1-y Fe2O4、Co y Ni 1-y Fe2O4-N / C and the corresponding adsorption model, such as Fig.12 In these models, the molecular linking groups are considered to be the main catalytic active sites. In addition, the corresponding simulated XRD patterns are calculated and shown in Fig.13 a and Fig.13 b. As in Fig.14 As shown in a, the XRD pattern of the as-prepared CoNiFe-N / Cx sample has characteristic peaks at 18.28°, 26.15°, 35.69° and 43.36°, which belong to the crystal plane (111) of CoFe2O4 (PDF#22-1086), the crystal plane (002) of N-doped carbon (PDF#50-1249), and the crystal plane (311) and crystal plane (400) of NiFe2O4 (PDF#10-0325), respectively, which is consistent with the previous HRTEM results. The Co was further studied by Raman spectroscopy. y Ni 1-y Fe2O4-N / C catalyst ( Fig.14 b) CoNiFe-x (except x≠1) is located at 2198cm -1 and 2225cm -1 The two peaks at 2+ )-Ni 3+ / 2+ and CN(Fe 3+ )-Ni 2+ Vibration of CoNiFe samples (except x≠0) at 2111cm -1 and 2143cm -1There are two similar signal peaks, which are respectively attributed to CN(Fe 2+ )-Co 3+ / 2+ and CN(Fe 3+ )-Co 2+ In addition, it is at 1346cm -1 and 1585cm -1 Two weak signals are shown at the point, corresponding to the D band and G band of carbon materials respectively.

[0126] The X-ray photoelectron spectroscopy (XPS) technique was used to investigate the y Ni 1-y Surface chemical state and bonding environment of Fe2O4-N / C samples. Fig.15 In a, XPS measurements of these catalysts confirmed the presence of Co, Ni, Fe, C, N, and O elements. The intensity of the Ni signal decreases with increasing Co ratio, which is consistent with the EDX analysis. High-resolution XPS spectra of Co 2p, Ni 2p, Fe 2p, C 1s, and N1s are shown in Fig.15 b to Fig.15 f. With the change of Co / Ni ratio, the binding energy of the three metals changes significantly. The peaks of Co and Ni move toward higher binding energy, while the Fe signal moves toward lower binding energy, indicating a strong trimetallic interaction. For the carbon layer, the C 1s peak of the CoNiFe-x sample is affected by the Co atomic content. In the corresponding N1s analysis ( Fig.15 f), the N 1s signal has a slight fluctuation. Fig.16 As shown in y Ni 1-y The four fitting peaks of the Fe2O4-N / C sample at 398.4, 399.5, 400.4 and 403.2 eV are attributed to pyridinic-N, metal-N, pyrrolic-N and oxidized-N, respectively, which confirms the formation of N-doped carbon layer. After quantitatively calculating the content of each N group ( Fig.17 a), it was found that higher percentage of metallic N may be beneficial to DMC and NRR, and more pyridinic N species promoted the efficiency of DMC. Fig.17 In b, the O 1s diagram shows a significant change in intensity and curve shape ( Fig.18 The O 1s signal can be divided into four peaks at 530.7, 531.9, 532.8 and 534.9 eV, corresponding to the lattice oxygen with metal (O Latt , OI), oxygen vacancies (O V , O-II), surface adsorbed oxygen (O ad , O-III) and COH (O-IV). In addition, Fig.17The percentage of each oxygen species is calculated in c, since surface adsorbed oxygen groups may play an important role in the electrochemical performance. Vacancy engineering indicates that oxygen vacancies are a promising strategy to enhance the activity of oxygen evolution reaction (OER). Impressively, in this work, higher oxygen vacancies do not seem to promote the performance of DMC. Fig.17 d, O Latt / O V The ratio of the curves shows a volcano-like trend, which reveals that O Latt / O V The highest value of is beneficial to improving NRR and DCM. This may be attributed to the trimetallic internal regulation effect that hinders the OER performance.

[0127] In order to evaluate the rate-determining steps of NRR and DCM on the CoNiFe-N / Cx catalyst surface, electrochemical impedance spectroscopy (EIS) was used to analyze the charge transfer under redox reaction conditions. Fig.19 a to Fig.19 As shown in c, the CoNiFe-N / C-0.8 catalyst exhibits the smallest semicircle, which indicates that it has excellent charge transfer on the electrode surface in the electrochemical NRR. Fig.19 c Inset) The EIS curves are fitted with the corresponding values ​​listed in Table 3 at various Co / Ni ratios. 0.8 Ni 0.2 Fe2O4-N / C catalyst exhibits the lowest charge transfer resistance (R ct ), R ct(CE) and R ct(AE) , thus proving that the optimized Co 0.8 Ni 0.2 The Fe2O4-N / C catalyst has excellent electron transfer ability in electrochemical NRR. Meanwhile, EIS measurements in 0.5 M Na2CO3 electrolyte ( Fig.19 d to Fig.19 f) reveals Co 0.6 Ni 0.4 Fe2O4-N / C has a lower R than other Co / Ni ratio catalysts. ct The minimum R of CoNiFe-N / C-0.6 catalyst ct The values ​​(Table 4) are consistent with the LSV measurements, where the highest anodic current density was achieved. y Ni 1-y The electrochemically active surface area (ECSA) of the Fe2O4-N / C catalyst was estimated based on its double-layer capacitance. Fig. 20 and Fig.21 The results show that the Co0.8 Ni 0.2 Fe2O4-N / C>Co 0.6 Ni 0.4 Fe2O4-N / C>Co 0.4 Ni 0.6 Fe2O4-N / C and Co 0.6 Ni 0.4 Fe2O4-N / C>Co 0.4 Ni 0.6 Fe2O4-N / C>Co 0.8 Ni 0.2 Fe2O4-N / C. Co for NRR 0.8 Ni 0.2 Fe2O4-N / C and Co for DMC 0.6 Ni 0.4 Fe2O4-N / C exhibited the highest ECSA, indicating that they possessed the most abundant electrochemically active sites for NRR and DMC, respectively. These electrochemical results indicate that the optimized catalysts for N2 reduction and CH4 oxidation are Co 0.8 Ni 0.2 Fe2O4-N / C and Co 0.6 Ni 0.4 Fe2O4-N / C.

[0128] To evaluate the electrochemical activities of the as-prepared CoNiFe-based catalysts for N2 reduction and CH4 oxidation, reduction and oxidation were carried out at room temperature using a graphite rod as the counter electrode in a homemade double chamber. Fig. 22 The chronoamperometric curves of CoNiFe-NC-0.8 for NRR are shown, showing that the current density increases with increasing cathode potential from −1.2 V to −1.6 V, which is consistent with Figure 3 The LSV results shown in a are consistent. Fig.23 As shown in a, Co 0.8 Ni 0.2 Fe2O4-N / C exhibited a maximum production rate of 52.35 μg h at -1.4 V (vs. Ag / AgCl). -1 mg cat. -1 of NH3 and the maximum FE is 15.35% at -1.3V (vs. Ag / AgCl). Compared with the CoNiFe-N / Cx sample at -1.4V (vs. Ag / AgCl) potential ( Fig.23 b), only the catalysts with x = 0.4, 0.6 and 0.8 showed catalytic activity for NRR, among which Co 0.8 Ni 0.2Fe2O4-N / C showed the best NRR performance. To investigate the effect of the carbon layer, the CoNiFe-x catalyst was also tested at the same potential of -1.4 V (vs. Ag / AgCl). Fig.23 As shown in c, 23.22 μg h -1 mg cat. -1 The highest NH3 production rate was obtained under CoNiFe-0.6, while the highest FE of 10.14% was obtained under CoNiFe-0.6. y Ni 1-y The interaction between Fe2O4 (y = 0.4, 0.6 and 0.8) and the carbon layer is beneficial to improve the NRR activity. The possible formation of by-products (N2H4) was further investigated using the Watt and Chrisp method. Fig.24 a presents a series of standard N2H4 graphs, showing that the absorbance of N2H4 increases linearly with increasing concentration. Fig.24 As shown in b, the UV-vis spectra of the solutions after two hours of electrolysis under Ar-saturated and N2-saturated conditions are almost the same; there is no absorbance change, confirming that the 0.8 Ni 0.2 In Fe2O4-N / C, no N2H4 was produced during NRR and N2 was reduced to NH3. On the other hand, the byproduct H2 was detected by gas chromatography (GC), indicating that hydrogen evolution reaction occurred at the cathode during NRR. Some recently reported promising Co / Ni / Fe-based catalysts for NRR, such as CoO QDs / rGO, 43 CoFe2O4 / rGO, 44 Single atom Co-N / C, 45 NiCo2O4-N / C, 46 Single atom Fe / NO / C, 47 and Fe-N / C-carbon nanotubes, 48 et al., indicating that the Co 0.8 Ni 0.2 Fe2O4-N / C exhibits excellent N2 reduction activity.

[0129] For CH4 oxidation in the anode compartment, Co 0.6 Ni 0.4 Fe2O4-N / C catalyst. DMC products were collected after two hours of electrolysis of CH4-saturated Na2CO3 solution at a potential of 0.8 V (vs. Ag / AgCl) and then 1 H NMR spectroscopy ( 1H NMR) analysis revealed that methanol and 2-propanol were detected with yields of 722.6 mmol g cat. -1 h -1 and 306.4mmol g cat. -1 h -1 , as listed in Table 6. In order to fully utilize both the anode reaction and the cathode reaction, an integrated electrochemical system was assembled and the cathode chamber was simultaneously charged with Co 0.8 Ni 0.2 NRR under Fe2O4-N / C and in the anode compartment under Co 0.6 Ni 0.4 The DMC under Fe2O4-N / C was tested, such as Fig.23 g. Fig.23 d shows the products collected after two hours of electrolysis at different potentials. 1 The H-NMR spectrum showed a strong peak, which was attributed to methanol. The intensity of this peak increased as the potential increased from 0.8 V to 1.1 V; however, when the potential was further increased to 1.2 V, its intensity decreased. Fig.23 d, a byproduct of 2-propanol was also observed. To further confirm the results, a control experiment was performed under the same conditions at open circuit potential for 2 h; 1 Methanol and 2-propanol were not detected in the H-NMR spectrum. The formation rates of methanol and 2-propanol were determined after two hours of electrolysis at different applied electrode potentials. Fig.23 e and Fig.25 As shown in Figure 2, methanol is the major product, and the highest yield rate obtained at 1.1 V (vs. Ag / AgCl) is 5070.7 mmol g cat. -1 h -1 , and the maximum selectivity was 82.8% at 0.8 V (vs. Ag / AgCl), with a yield of 1925.47 mmol g cat. -1 h -1 .exist Fig.23 The FEs for methanol and 2-propanol production are presented in Fig. 5; the highest FE for methanol production (9.02%) was achieved at 0.8 V, while the highest FE for 2-propanol formation (6.94%) was obtained at 0.9 V. As shown in Table 6, the yield and FE of methanol increased by 2.7 and 2.4 times, respectively, compared to those measured in the absence of NRR, while the improvement for 2-propanol was weak. Fig.23 h shows some improvement in the anode current density measured from LSV. The effect of the integrated electrochemical system on NRR was also examined (Table 7), indicating a 1.6-fold increase in the NH3 production rate. The stability of the two integrated electrochemical processes was further tested ( Fig.23 i), showing high stability during the 12 h electrolysis period. The above results indicate that the integrated electrochemical system is effective for simultaneously performing NRR in the cathode compartment and DMC in the anode compartment. This is compared with the published work on DMC at various anode materials (Table 8), such as TiO2, 18 Nickel-based catalysts, 15、 23 ZrO2-based catalysts, 13、14、24 and CuO / CeO2 catalyst, 19 Co 0.6 Ni 0.4 The Fe2O4-N / C catalyst showed the best conversion of CH4 to CH3OH.

[0130] Explore the prepared Co y Ni 1-y The electronic structures of Fe2O4-N / C NC catalysts and the appropriate Co / Ni molar ratio were investigated by density functional theory (DFT) calculations to reveal the influence of Co on the catalyst performance. 0.6 Ni 0.4 Fe2O4-N / C and Co 0.8 Ni 0.2 Adsorption energies of DMC and NRR on Fe2O4-N / C. The obtained electron paramagnetic resonance (EPR) spectra ( Fig.26 ) combined with previous work, 9 Superoxide free radicals (·O2 - ) was identified as the active substance, thus proving that Co 0.6 Ni 0.4 Fe2O4-N / C can selectively activate CH4 to form CH3. In addition, the adsorption energy of CH4 on the surfaces of CoNiFe-x and CoNiFe-N / Cx was calculated by Equation S11 in the Supporting Information. Fig. 27 As shown in 0.6 Ni 0.4 The Fe2O4-N / C catalyst exhibited the lowest CH4 adsorption energy, which confirmed that it could serve as a viable catalyst for the efficient activation of CH4. As Ma et al. 24 and Park et al. 13 As demonstrated in their study, if the methanol product happens to be overoxidized to 1-propanol or 2-propanol, 1 Formaldehyde or acetaldehyde intermediates were easily detected in the H-NMR spectrum; however, there were no signals associated with the generation of these two by-products. 1 H-NMR results and information, 22 The simultaneous reaction pathways of DMC and NRR can be summarized as follows:

[0131] Integrated electrochemical system:

[0132] anode:

[0133] CH4 + 2OH - → CH3OH + H2O + 2e - (1)

[0134] 3CH4 + 6OH - → CH3CHOHCH3 + 5H2O + 6e - (2)

[0135] 4OH - → 2H2O + O2 + 4e - (3)

[0136] cathode:

[0137] N2 + 6H2O + 6e - → 2NH3 + 6OH - (4)

[0138] 2H2O + 2e - → H2 + 2OH - (5)

[0139] In this integrated system, CH4 is heated to 1.5 % in the anode chamber. 0.6 Ni 0.4 The active free radicals (·O2 - ) is selectively oxidized to methanol and 2-propanol, which is attributed to the trimetallic-carbon layer interaction. The electrons generated by the anodic oxidation reactions (1)–(3) are transferred to the cathode Co 0.8 Ni 0.2 Fe2O4-N / C, which promotes the cathode reduction of (4) and (5). Subsequently, the possible mechanism of the combined electrochemical system can be presented in Scheme 2. Fig.28 The electron transfer pathways during CH4 and NRR over the optimized catalysts were also explored. 0.6 Ni 0.4 The partial density of states (PDOS) of CH4 oxidation on the Fe2O4-N / C surface shows highly concentrated electrons, and the shape of the electron orbital distribution also changes significantly after the adsorption of CH4 molecules. 0.6 Ni 0.4 The overlap of the -3d band, Fe 3d band, and O 2p band indicates a strong coupling between the trimetal and oxygen. In addition, after CH4 activation, the electron density difference (EDD) mapping indicates that the generated electrons will be quickly transferred to Co 0.6 Ni 0.4Atomically, such as Fig.28 c is shown in the inset. In addition, the PDOS of the carbon layer ( Fig.29 a and Fig.29 b) Revealing that N-doped carbon plays a key role in electron transfer because it provides an efficient electron transfer channel. 0.6 Ni 0.4 and Fe are therefore considered to be the main catalytic centers of DMC. And under NRR conditions, Co 0.8 Ni 0.2 Co in Fe2O4-N / C 0.8 Ni 0.2 The main peak intensity of is reduced due to electron transfer with N2 ( Fig.28 d) At the same time, Co 0.8 Ni 0.2 The fluctuation and superposition of the -3d band and O-2p band indicate that N2 molecules can be easily absorbed by Co 0.8 Ni 0.2 The active sites and active oxygen groups are activated, which is consistent with the EDS mapping, where the Co 0.8 Ni 0.2 The released electrons are transferred to N2. Fig.29 c and Fig.29 d, from Co 0.8 Ni 0.2 The PDOS catalyst of Fe2O4-N / C carbon layer reveals that the intensity of N-2p band increases with the adsorption of N2, indicating that it accelerates electron transfer. The DFT results prove that the interaction between trimetallic CoNiFe and carbon layer greatly improves the performance of CH4 oxidation and N2 reduction.

[0140]

[0141] Electrochemical activity evaluation

[0142] A two-chamber cell separated by a pretreated cation exchange membrane (CEM) was used to study the products of each chamber. When a single reduction or oxidation reaction was studied in one chamber, the other chamber was examined without gas bubbling. For NRR experiments, a graphite rod was used as the counter electrode. In the cathode chamber with N2 gas, the production of ammonia (NH3) was measured and quantified by a modified indophenol blue method. 1,2 As follows, 2 mL of the cathode effluent was taken, and then 2 mL of solution A (10.0 g salicylic acid and 10.0 g sodium citrate dissolved in 0.32 M NaOH solution), 1 mL of 0.05 M NaClO, and 0.2 mL of 0.01 g mL -1C5FeN6Na2O was added dropwise to the test solution. After 2 hours, the concentration was measured at 655 nm by UV-vis spectrophotometer (Varian Cary 50). 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 μg mL -1 The calibration curve was generated by comparing the standard NH4Cl with the corresponding UV-vis absorbance, and a clear linear relationship (y = 0.113x + 0.013, R 2 =0.999). Each time, the open circuit condition and Ar saturated condition of the NRR experiment were considered as the baseline for the NH3 yield calculation to avoid any exogenous nitrogen compound sources. 3 Optimized C in NRR [NH3] The resulting calculation is as follows:

[0143]

[0144] in They were obtained under N2 saturated conditions, Ar saturated conditions and open circuit conditions in the NRR experiment respectively.

[0145] The NH3 yield was calculated by the following equation:

[0146]

[0147] in is the obtained NH3 concentration; V is the reaction electrolyte solution (20mL); m cat. is the mass of the catalyst, and t is the time of the electrolysis reaction (t=2h).

[0148] The Faradaic efficiency is calculated as follows:

[0149]

[0150] Where F is the Faraday constant (96485.3C mol -1 ); Q is the charge of the applied potential band. In addition, the possible by-product (N2H4) was also investigated by our previously reported method. 4 There was no change at 455 nm in the UV-vis spectrum at the beginning and 2 h of NRR, indicating that there was no N2H4 generation in this system.

[0151] In the anode chamber, the CH4 oxidation reaction was studied. Pure CH4 gas was injected at a rate of 5 mL min -1 The flow rate of 2.5 % was continuously purged into 0.5 M Na2CO3 electrolyte. All gas products were detected by gas chromatography. The 1 H NMR spectroscopy (1 H NMR) was used to analyze the liquid products of CH4 electrochemical oxidation. Before measurement, 0.35 mL of sample from the anode chamber was mixed with 0.05 wt% tetramethylsilane (TMS) in 0.35 mL D2O. The product yield, FE, corresponding selectivity and CH4 conversion were calculated as follows:

[0152] Yield (mmol g cat. -1 h -1 ) = mmol product / g catalyst / h reaction time (S4)

[0153] FE(CH3OH,%)=0.1929*n(CH3OH,μmol)*100% / Q(S5)

[0154] FE(CH3CHOHCH3,%)=0.1929*n(CH3CHOHCH3,μmol)*100% / Q(S6)

[0155] Selectivity of CH3OH = 100% * n(CH3OH) / (n(CH3OH)+n(CH3CHOHCH3)(S7)

[0156] Selectivity of CH3CHOHCH3 = 100% * n(CH3CHOHCH3) / (n(CH3OH)+n(CH3CHOHCH3)(S8)

[0157] Where Q is the total charge.

[0158] The integrated reaction system consists of two working electrodes and one reference electrode. 0.8 Ni 0.2 Fe2O4-N / C and Co 0.6 Ni 0.4 Fe2O4-N / C catalysts were used as working electrodes in the cathode chamber and the anode chamber, respectively. N2 gas and CH4 gas were purged into the corresponding electrolytes simultaneously. Considering the measurement of current density, the reference electrode will be used in the same chamber as the target reaction. After two hours of electrolysis, the corresponding anolyte and catholyte will be collected and further analyzed. In order to exclude possible interference, a blank experiment was performed, including blank GCE and NiCoFe catalyst under open circuit potential conditions.

[0159] Characterization of Nanomaterials

[0160] The morphology of the CoNiFe-N / C and CoNiFe catalysts was characterized using field emission scanning electron microscopy (FE-SEM) (FEIQuanta 250) and high-resolution transmission electron microscopy (HRTEM) (FEI Tecnai F30 electron microscope, using an accelerating voltage of 200 kV). The crystalline structure of the as-prepared catalysts was studied using an X-ray diffractometer with Cu Kα radiation (D / max-2400, Japan, with a light source wavelength (λ) of 0.1541 nm). The morphology of the as-prepared catalysts was characterized using an X-ray diffractometer with monochromatic Al K α The chemical composition and oxidation state were analyzed by X-ray photoelectron spectroscopy (XPS) with an X-ray source (Scienta Omicron). Raman spectra were recorded at 532 nm using a Raman spectrophotometer (Renishaw Canada Ltd.). A QMA200M thermal analyzer (METTLER TOLEDO) was used under air conditions at 2 °C min -1 Thermogravimetric (TG) analysis was performed at a heating rate of 1.5 %. Free radicals were detected via electron paramagnetic resonance (EPR) spectroscopy, which was performed using a Bruker ECS106 X-band spectrometer (Bruker A200, Germany). Gas products were transferred using a gas-tight syringe (Hamilton) and examined using a gas chromatograph (GC, Shimadzu, GC-2014, column: silica gel) equipped with a thermal conductivity detector (TCD).

[0161] Theoretical calculations

[0162] To explore the electronic structure and electron transfer in NRR and CH4 oxidation systems, a Co nanostructured carbon nanotube was constructed based on a NiFe2O4 template. y Ni 1-y Fe2O4 and Co y Ni 1-y Fe2O4-N / C model. The optimization of the constructed structure was achieved by the CASTEP module with the Perdew-Burke-Ernzerhof (PBE) function of the generalized gradient approximation (GGA). In addition, the positions of Co doping were considered to replace Ni atoms with Co atoms. The 2×2×1 3D triclinic NiFe2O4 unit cell ( α=β=γ=90°) is used for doping and addition of carbon layer unit cells. A 2×1×1 k-point set and an energy cutoff of 320 eV are implemented to optimize the geometry of the constructed model with a medium k-point set. The convergence criterion for energy is 1.0×10 -5 eV, and the force convergence criterion is The adsorption energy (E) is calculated as follows:

[0163]

[0164] in E 碳层 , and E H Co y Ni 1-y Fe2O4-N / C、Co y Ni 1-y Electronic energies of the Fe2O4, carbon, CH4, and H unit cells. For the first principle calculations of the activation of CH4 to CH3, an energy cutoff of 350 eV was performed. The force tolerance, SCF tolerance, and electric field are 1.0×10 per atom -5 eV and -5 eV (relative to vacuum). The experimental optimum potential of the electrode reaction was determined by adding the value of -neU (n: number of electrons in DMC; U: potential).

[0165] Although the present disclosure has been described with reference to what are presently considered to be preferred examples, it should be understood that the application is not limited to the examples described herein. Instead, the present disclosure is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0166] All publications, patents, and patent applications herein are incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference in its entirety. When a term in the present disclosure is found to be defined differently in a document incorporated by reference, the definition provided herein will serve as the definition for that term.

[0167] References

[0168] 1. Z. Wang, Y. Li, H. Yu, Y. Xu, H. Xue, X. Li, H. Wang and L. Wang, ChemSusChem, 2018, 11, 3480-3485.

[0169] 2. L. Xia, X. Wu, Y. Wang, Z. Niu, Q. Liu, T. Li, X. Shi, AMAsiri and

[0170] 3.SZAndersen,V.Colic,S.Yang,JASchwalbe,ACNielander,JMMcEnaney,K.Enemark-Rasmussen,JGBaker,ARSingh,BARohr,MJStatt,SJBlair,S.M ezzavilla,J.Kibsgaard,PCKVesborg,M.Cargnello,SFBent,TFJaramillo,IELStephens,JKNorskov&I.Chorkendorff,Nature,2019,570,504-508.

[0171] 4. L. Zeng, X. Li, S. Chen, J. Wen, W. Huang and A. Chen, J. Mater.Chem.A, 2020, 8, 7339-7

[0172] 5.X.Han,CSGerke,S.Banerjee,M.Zubair,JJiang,NMBedford,EMMillerandVSThoi,ACS Energy Lett.,2020,5,3237-3243.

[0173] 6. K. Chu, Y. P. Liu, Y. B. Li, H. Zhang, and Y. Tian, ​​J. Mater.Chem.

[0174] 7. MIAhmed, S. Chen, W. Ren, X. Chen, and C. Zhao, Chem.Commun.

[0175] 8. J. Hou, M. Yang, and J. Zhang, Nanoscale, 2020, 12, 6900-6

[0176] 9. S. Luo, X. Li, B. Zhang, Z. Luo&M. Luo, ACS Appl.Mater.Interfaces, 2019,11,26891-26897.

[0177] Energy Environ.Sci., 2021, 14, 672-687.

[0178] 11. K. Chu, Y.-p. Liu, Y.-b. Li, Y.-l. Guo, and Y. Tian, ACS Appl. Mater. Interfaces, 2020, 12, 7081 - 7090.

[0179] 12. K. Lu, F. Xia, B. Li, Y. Liu, I. B. Abdul Razak, S. Gao, J. Kaelin, D. E. Brown, and Y. Cheng, ACS Nano, 2021.

[0180] 13. K. Zhao, X. Quan, Y. Su, X. Qin, S. Chen, and H. Yu, Environ. Sci. Technol., 2021.

[0181] 14. F. Lai, J. Feng, X. Ye, W. Zong, G. He, C. Yang, W. Wang, Y.-E. Miao, B. Pan, W. Yan, T. Liu, and I. P. Parkin, J. Mater. Chem. A, 2020, 8, 1652 - 1659.

[0182] 15. C. Ma, X. Yan, H. He, B. Liu, and S. Yan, Sustain. Energy Fuels, 2021, 5, 2415 - 2418.

[0183] 16. J. H. Moon, M. Y. Lee, B. C. Park, Y. S. Jeon, S. Kim, T. Kim, M. J. Ko, K. H. Cho, K. T. Nam, and Y. K. Kim, Small, 2021, e2103575.

[0184] 17. C. Li, Y. Fu, Z. Wu, J. Xia, and X. Wang, Nanoscale, 2019, 11, 12997 - 13006.

[0185] 18. Y. Li, J. Li, J. Huang, J. Chen, Y. Kong, B. Yang, Z. Li, L. Lei, G. Chai, Z. Wen, L. Dai, and Y. Hou, Angew. Chem. Int. Ed., 2021, 60, 9078 - 9085.

[0186] 19. W. Ye, Y. Yang, M. Arif, S. Yang, X. Fang, M. A. Mushtaq, X. Chen and D. Yan, ACS Sustainable Chem. Eng., 2020, 8, 15946 - 15952.

[0187] 20. Y. Wang, X. Cui, J. Zhao, G. Jia, L. Gu, Q. Zhang, L. Meng, Z. Shi, L. Zheng, C. Wang, Z. Zhang and W. Zheng, ACS Catal., 2018, 9, 336 - 344.

[0188] 21. W. Li, D. He, G. Hu, X. Li, G. Banerjee, J. Li, S. H. Lee, Q. Dong, T. Gao, G. W. Brudvig, M. M. Waegele, D. E. Jiang and D. Wang, ACS Cent Sci, 2018, 4, 631 - 637.

[0189] 22. Y. Song, Y. Zhao, G. Nan, W. Chen, Z. Guo, S. Li, Z. Tang, W. Wei and Y. Sun, Appl. Catal. B - Environ., 2020, 270, 118888.

[0190] 23. Z. Guo, W. Chen, Y. Song, X. Dong, G. Li, W. Wei and Y. Sun, Chinese J. Catal., 2020, 41, 1067 - 1072.

[0191] 24. Y. Liu, X. Zhu, Q. Zhang, T. Tang, Y. Zhang, L. Gu, Y. Li, J. Bao, Z. Dai and J.-S. Hu, J. Mater. Chem. A, 2020, 8, 8920 - 8926.

[0192] 25. M. Ma, C. Oh, J. Kim, J. H. Moon and J. H. Park, Appl. Catal. B - Environ., 2019, 259, 118095.

[0193] 26. M. Ma, B. J. Jin, P. Li, M. S. Jung, J. I. Kim, Y. Cho, S. Kim, J. H. Moon and J. H. Park, Adv. Sci., 2017, 4, 1700379.

[0194] 27. C. Oh, J. Kim, Y. J. Hwang, M. Ma and J. H. Park, Appl. Catal. B-Environ., 2021, 283, 119653.

[0195] 28. J. Wu, JHLi and YXYu, ACS Appl. Mater. Interfaces, 2021, 13, 10026-10036.

[0196] 29. J. Lee, J. Yang and JHMoon, ACS Energy Letters, 2021, 893-899.

[0197] Table 1. Co after high temperature treatment in air or Ar y Ni 1-y -Productivity of Fe-PBA catalyst.

[0198]

[0199] Table 2. Different Co y Ni 1-y EDX Analysis of Fe2O4-N / C Catalyst

[0200]

[0201] Table 3. Co y Ni 1-y Parameter Analysis of the Equivalent Circuit Model Corresponding to the Nyquist Diagram of Fe2O4-C / N under N2 Saturation Conditions

[0202]

[0203] R ohm = Solution resistance, R ct(CE) = Charge transfer resistance, R ct(AE) = charge transfer and recombination resistance, C = double layer capacitance, W = Warburg impedance (mass transfer).

[0204] Table 4. Co y Ni 1-y Parameter analysis of the equivalent circuit model corresponding to the Nyquist diagram of Fe2O4-C / N under CH4 saturation conditions.

[0205]

[0206] R ohm = Solution resistance, R ct(CE) = Charge transfer resistance, R ct(AE)= charge transfer and recombination resistance, C = double layer capacitance, W = Warburg impedance (mass transfer).

[0207]

[0208] Table 6. Comparison of CH4 oxidation performance at 0.8 V (vs. Ag / AgCl) for 2 h in the cathode chamber with or without N2 gas flow.

[0209]

[0210] 1 Unit: mmol g cat -1 h -1 , 2 Unit: mA cm -2 .

[0211] Table 7. Comparison of 2h NRR performance at -0.8 V (vs. Ag / AgCl) with or without CH4 gas in the anode.

[0212]

[0213] Table 8. Summary of electrocatalytic CH4 oxidation systems at room temperature.

[0214]

Claims

1. An electrochemical catalyst comprising: (i) a trimetallic oxide of the following formula Co 1-x Ni x Fe2O4 The catalyst is in the form of nanocubes and x is an integer between 0.1 and 0.9; and (ii) Carbon.

2. The electrochemical catalyst according to claim 1, wherein the trimetallic oxide is Co 0.8 Ni 0.2 Fe2O4.

3. The electrochemical catalyst according to claim 1, wherein the trimetallic oxide is Co 0.6 Ni 0.4 Fe2O4.

4. The electrochemical catalyst according to claim 1, wherein the catalyst has XRD peaks at 18.28°, 26.15°, 35.69° and 43.36°.

5. The electrochemical catalyst according to any one of claims 1 to 4, wherein x is an integer between 0.01 and 0.

99.

6. The electrochemical catalyst of claim 5, wherein x is about 0.20, about 0.40, about 0.60, or about 0.

80.

7. The electrochemical catalyst according to any one of claims 1 to 6, wherein the carbon is elemental carbon.

8. The electrochemical catalyst according to claim 7, wherein the elemental carbon is graphite or graphene.

9. The electrochemical catalyst according to any one of claims 1 to 8, wherein the carbon is in the form of a layer adjacent to the nanocube.

10. The electrochemical catalyst of claim 9, wherein the size of the nanocubes with adjacent carbon layers is between 10 nm and 1000 nm 11. The electrochemical catalyst of claim 10, wherein the size of the nanocubes with adjacent carbon layers is between 500 nm and 700 nm.

12. The electrochemical catalyst of claim 11, wherein the size of the nanocubes with adjacent carbon layers is between 600 nm and 700 nm.

13. The electrochemical catalyst of claim 12, wherein the size of the nanocubes with adjacent carbon layers is between 640 nm.

14. A method for producing methanol from methane in an electrochemical process, the process comprising: (e) introducing methane into an anode chamber of an electrochemical reactor, wherein the anode chamber comprises an anode comprising an electrochemical catalyst according to any one of claims 1 to 13; (f) introducing a catholyte into a cathode chamber of the electrochemical reactor, wherein the cathode chamber comprises a cathode; (g) introducing a voltage between the anode and the cathode, thereby oxidizing at least a portion of the methane to methanol; and (h) collecting the methanol from the anode chamber.

15. The method of claim 14, wherein the process further produces isopropanol.

16. The method according to claim 14, wherein the electrochemical catalyst is Co 0.6 Ni 0.4 Fe2O4.

17. The method of claim 14, wherein the applied potential is between 0.2 V and 2.5 V vs. Ag / AgCl.

18. A method for producing ammonia from nitrogen (N2) in an electrochemical process, the process comprising: (e) introducing ammonia into a cathode chamber of an electrochemical reactor, wherein the cathode chamber comprises a cathode comprising an electrochemical catalyst according to any one of claims 1 to 13; (f) introducing an anolyte into an anode compartment of the electrochemical reactor, wherein the anode compartment comprises an anode; (g) introducing a voltage between the anode and the cathode, thereby reducing at least a portion of the nitrogen to ammonia; and (h) collecting the ammonia from the cathode chamber.

19. The method according to claim 18, wherein the electrochemical catalyst is Co 0.8 Ni 0.2 Fe2O4.

20. The method of claim 18, wherein the applied potential is between 0.0 V and -2.0 V vs. Ag / AgCl.

21. A method for producing methanol from methane and ammonia from nitrogen in an electrochemical process, the process comprising: (e) introducing methane into an anode chamber of an electrochemical reactor, wherein the anode chamber comprises an anode comprising an electrochemical catalyst according to any one of claims 1 to 13; (f) introducing ammonia into a cathode chamber of an electrochemical reactor, wherein the cathode chamber comprises a cathode comprising an electrochemical catalyst according to any one of claims 1 to 13; (g) introducing a voltage between the anode and the cathode, thereby oxidizing at least a portion of the methane in the anode chamber to methanol and reducing at least a portion of the nitrogen in the cathode chamber to ammonia; as well as (h) collecting the methanol from the anode chamber and collecting the ammonia from the cathode chamber.

22. The method according to claim 21, wherein the electrochemical catalyst in the anode chamber is Co 0.6 Ni 0.4 Fe2O4.

23. The method according to claim 21, wherein the electrochemical catalyst in the cathode chamber is Co 0.8 Ni 0.2 Fe2O4.